A report on occurrence of freshwater sponge Eunapius carteri (Bowerbank,1863) in Pravara River, Maharashtra, India - Geetanjali R. Devdhe,; Unmesh S. Adkar,; Ananta D. Harkal, (The Bioscan, 2025)
The scientific investigation of Freshwater Sponges showed limited study due to their scarce recorded presence when compared to marine species. A study identifies Eunapius carteri in its new discovery from the Pravara River located in Ahilyanagar (Formerly Ahmednagar) district of Maharashtra India. Researchers identified Freshwater Sponges using SEM to analyze both the colony structure and spicule and gemmule appearance. The examination site consisted of Sponges that adhered to underwater plants. This work presents internal morphological views of gemmules through SEM, as it is a key diagnostic feature.